2020
DOI: 10.5946/ce.2019.184
|View full text |Cite
|
Sign up to set email alerts
|

Present Status of Endoscopic Submucosal Dissection for Non-Ampullary Duodenal Epithelial Tumors

Abstract: Prediction of histology by endoscopic examination is important in the clinical management of non-ampullary duodenal epithelial tumors (NADETs), including adenoma and adenocarcinoma. The use of a simple scoring system based on the findings of white-light endoscopy or magnified endoscopy with narrow-band imaging is useful to differentiate between Vienna category 3 (C3) and C4/5 lesions. Less invasive endoscopic resection procedures, such as cold snare polypectomy, are quick to perform and convenient for small (<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 23 publications
0
22
0
1
Order By: Relevance
“…Furthermore, most patients with duodenal cancer are diagnosed at an advanced stage, resulting in a poor prognosis 5–7 . With advances in endoscopic equipment and increasing awareness of duodenal tumors, attention to this field has been increasing worldwide 8–12 . The number of patients with duodenal cancer has been gradually increasing 6,13 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, most patients with duodenal cancer are diagnosed at an advanced stage, resulting in a poor prognosis 5–7 . With advances in endoscopic equipment and increasing awareness of duodenal tumors, attention to this field has been increasing worldwide 8–12 . The number of patients with duodenal cancer has been gradually increasing 6,13 .…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic treatment, as the main treatment method for tumors less than 1 cm, has the signi cant advantages of short operation time, low cost, short hospital stay, and less impact on quality of life [9].…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the thin wall of the duodenum and its rich blood vessels, most tumors invade the submucosa. Therefore, duodenal endoscopic submucosal dissection is truly challenging, and even Japanese experts think twice before indicating [11], because there are risks of bleeding, perforation, positive margins, and missed metastatic lymph nodes in endoscopic resection treatment [8,9,[12][13][14][15][16]. Some studies reported that the lymphatic metastasis rate of d-NET with a tumor of 1-2 cm in diameter was approximately 60% [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Recent small case series have demonstrated a good safety and efficacy profile for combined laparoscopic and endoscopic surgery in patients with advanced duodenal adenomas or early adenocarcinomas [88][89][90][91][92]. Ichikawa et al [92] reported no local or distant recurrence at a median follow-up of 14 months RECOMMENDATION ESGE suggests that, in expert hands, endoscopic fullthickness resection could be an alternative to surgery or ESD for select cases of nonlifting duodenal adenomas up to 25 mm in size without signs of deep submucosal invasion.…”
Section: Alternative Modalities To Emr or Esd For Duodenal Adenomasmentioning
confidence: 99%